2014
DOI: 10.1128/iai.01498-14
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Mutants of Francisella tularensis Protect Rabbits against Aerosol Challenge with a Virulent Type A Strain

Abstract: c Francisella tularensis, a Gram-negative bacterium, is the causative agent of tularemia. No licensed vaccine is currently available for protection against tularemia, although an attenuated strain, dubbed the live vaccine strain (LVS), is given to at-risk laboratory personnel as an investigational new drug (IND). In an effort to develop a vaccine that offers better protection, recombinant attenuated derivatives of a virulent type A strain, SCHU S4, were evaluated in New Zealand White (NZW) rabbits. Rabbits vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 47 publications
8
40
1
1
Order By: Relevance
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (46). The survival of LVS-vaccinated rabbits and consistent/higher SF from the aerosol characterization studies both argue that BHI should be used in pivotal Ft efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (46). The survival of LVS-vaccinated rabbits and consistent/higher SF from the aerosol characterization studies both argue that BHI should be used in pivotal Ft efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionsupporting
confidence: 58%
“…One argument against using the rabbit for tularemia vaccine studies had been that vaccination with LVS extended time to death but not survival (5, 6, 10, 21). Our own prior studies are included in those findings, including the observation that oral inoculation or inhalation of LVS did extend rabbit time to death more than subcutaneous inoculation (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of death in the rabbits appeared to be severe septic shock and/or acute respiratory distress syndrome. Additionally, we have shown that attenuated strains of F. tularensis can protect rabbits against aerosol challenge with virulent SCHU S4 (4)(5)(6). The degree of protection against morbidity and mortality is a function of the attenuated strain used, the number of vaccinations, and the route of vaccination.…”
mentioning
confidence: 99%
“…The name of the bacterium comes from the name of the researcher, Dr. Edward Francis, dealing with these pathogens (McCoy and Chapin 1912). Although the micro-organism is pathogenic to 190 species of "animals", clinical symptoms occur mainly in lagomorphs and rodents (Glinski and Kostro 2005, Reed et al 2014). The natural reservoirs are murine, muskrats, water rats, ground squirrels, voles and rabbits (Rastawicki and Jagielski 2005, Osiak et al 2006).…”
Section: Introductionmentioning
confidence: 99%